Assessment of the mechanics of a tissue-engineered rat trachea in an image-processing environment - Da Silva, Thiago Henrique Gomes; Pazetti, Rogerio; Aoki, Fabio Gava; Cardoso, Paulo Francisco Guerreiro; Valenga, Marcelo Henrique; Deffune, Elenice [UNESP]; Evaristo, Thaiane; Pêgo-fernandes, Paulo Manuel; Moriya, Henrique Takachi (Universidade de São Paulo (USP), Faculdade de Medicina, 2014)
OBJECTIVES: Despite the recent success regarding the transplantation of tissue-engineered airways, the mechanical properties of these grafts are not well understood. Mechanical assessment of a tissue-engineered airway graft before implantation may be used in the future as a predictor of function. The aim of this preliminary work was to develop a noninvasive image-processing environment for the assessment of airway mechanics.METHOD: Decellularized, recellularized and normal tracheas (groups DECEL, RECEL, and CONTROL, respectively) immersed in Krebs-Henseleit solution were ventilated by a small-animal ventilator connected to a Fleisch pneumotachograph and two pressure transducers (differential and gauge). A camera connected to a stereomicroscope captured images of the pulsation of the trachea before instillation of saline solution and after instillation of Krebs-Henseleit solution, followed by instillation with Krebs-Henseleit with methacholine 0.1 M (protocols A, K and KMCh, respectively). The data were post-processed with computer software and statistical comparisons between groups and protocols were performed.RESULTS: There were statistically significant variations in the image measurements of the medial region of the trachea between the groups (two-way analysis of variance [ANOVA], p<0.01) and of the proximal region between the groups and protocols (two-way ANOVA, p<0.01).CONCLUSIONS: The technique developed in this study is an innovative method for performing a mechanical assessment of engineered tracheal grafts that will enable evaluation of the viscoelastic properties of neo-tracheas prior to transplantation.
Keywords: Instrumentation; Respiratory Mechanics; Trachea